Navigating the Religious Gender Binary - Darwin, Helana (Sociology of religion, 2020)
This study illustrates the regulatory impact of binary gender ideology upon religious practitioners through interview data from 44 religious and formerly religious nonbinary people (who do not identify as simply men or women). Results indicate that nonbinary people who wish to maintain religious ties must either adjust religion to accommodate their nonbinary gender or accept misgendering to accommodate their religious tradition, with very few alternative options. They must overcome ideological, liturgical, and ritual obstacles while navigating the regulatory barrier that this article calls "the religious gender binary." Challenges intensify for religious minorities in practice-based traditions due to structural constraints. These findings contribute toward the sociology of religion by (1) demonstrating how nonbinary people experience the binary (cis)gendering of reality across religious traditions and (2) illuminating the need for more research that centers gender minorities and religious minorities, as the sociology of gender and religion expands beyond cisnormative and Christonormative frameworks.